Endothelial Cdc42 deficiency impairs endothelial regeneration and vascular repair after inflammatory vascular injury - Lv, Jiawen (Respir Res, 2018)
BACKGROUND: Endothelial cell (EC) regeneration is essential for inflammation resolution and vascular integrity recovery after inflammatory vascular injury. Cdc42 is a central regulator of cell survival and vessel formation in EC development. However, it is unknown that whether Cdc42 could be a regulating role of EC repair following the inflammatory injury in the lung. The study sought to test the hypothesis that Cdc42 is required for endothelial regeneration and vascular integrity recovery after LPS-induced inflammatory injury. METHODS AND RESULTS: The role of Cdc42 for the regulation of pulmonary vascular endothelial repair was tested in vitro and in vivo. In LPS-induced acute lung injury (ALI) mouse models, knockout of the Cdc42 gene in ECs increased inflammatory cell infiltration and pulmonary vascular leakage and inhibited vascular EC proliferation, which eventually resulted in more severe inflammatory lung injury. In addition, siRNA-mediated knockdown of Cdc42 protein on ECs disrupted cell proliferation and migration and tube formation, which are necessary processes for recovery after inflammatory vascular injury, resulting in inflammatory vascular injury recovery defects. CONCLUSION: We found that Cdc42 deficiency impairs EC function and regeneration, which are crucial in the post-inflammatory vascular injury repair process. These findings indicate that Cdc42 is a potential target for novel treatments designed to facilitate endothelial regeneration and vascular repair in inflammatory pulmonary vascular diseases, such as ALI/ARDS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12931-018-0729-8) contains supplementary material, which is available to authorized users.